Lateral capacity of segmental model piles under cyclic loading - Sengez, Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Short piles produced with traditional methods are rigid because of the used materials. In this study segmental piles with low rigidity are used. Behavior of these piles are examined under cyclic loading. The segmental pile is formed of the mortar blocks, rubber materials and rescale films which are placed between the mortar blocks and rubber material. The pile is exposed to three point bending test in order to control the target rigidity value. Also with the prescale films stress values are measured. The stress values are used for the moment calculation validation. The stress values are used for the moment calculation validation. Then the segmental pile is placed in the box and around the pile is filled with sand in different density stages. Cyclic loading is made with the antagonistic testing device operate with pneumatic muscles. Displacement values are measured under the applied load. Mortar beam is used for control and the displacement results are compared. From the load-deflection/interface relationship for rubber shore 60 tests shear values corresponding to displacement values are calculated. Shear values are integrated to obtained moment values.
Keywords: Piling (Civil engineering)